Psychology in Malaysia : looking ahead - Ansari, Zafar Afaq; Noor, Noraini M.; Haque, Ambar (Thomson, 2005)
Psychology touches almost every aspect of our lives, from the self to the family and to society as a whole. lVhat is our nature, how is personality developed or shaped, and why do people behave the way they do? Why and how are people different in their intelligence and temperaments and can we treat abnonnal behaviors with psychological techniques? These and many other questions arise in our minds at least some time in our lives. Especially in the modern world when man has advanced tremendously in science and technolog}~ he has yet to comprehend his own selfand his fellow beings for increased selfand mutual understanding that would hopefully result in a more harmonious world. There are many views on human behaviors and mental processes offered by psychologists. The development of modem psychology has taken place mostly in the West, particularly in the United States